Family outcomes in early intervention: results from a nationwide study in Portugal - Leite, Carina Sofia Correia (2020)
Several studies have stressed the outcomes for families who are supported by Early Intervention in the following dimensions: knowledge/information; development of competencies; well-being; and quality of life. As a result, this study assessed 999 families to examine the outcomes of Early Intervention in Portugal. Our results show that families supported by Early Intervention benefit in dimensions related to the development of competencies in the child and the family, and to the gain of information and knowledge about support and community resources, which results in perceived control and co-responsibility. The analysis of the outcomes of Early Intervention also shows that parents’ education and occupation levels are determining variables for a family to benefit from the positive impact of Early Intervention. In light of such results, we present recommendations for practices in the area of Early Intervention with the aim of adapting the practices of professionals to the concerns and priorities of Portuguese families.